2019
DOI: 10.3389/fnins.2019.00403
|View full text |Cite
|
Sign up to set email alerts
|

L-Lactate Promotes Adult Hippocampal Neurogenesis

Abstract: Neurogenesis, the formation of new neurons in the adult brain, is important for memory formation and extinction. One of the most studied external interventions that affect the rate of adult neurogenesis is physical exercise. Physical exercise promotes adult neurogenesis via several factors including brain-derived neurotrophic factor (BDNF) and vascular endothelial growth factor (VEGF). Here, we identified L -lactate, a physical exercise-induced metabolite, as a factor that promotes adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
76
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(84 citation statements)
references
References 87 publications
3
76
1
Order By: Relevance
“…It has been demonstrated that physical exercise increases BDNF levels 45. Thus, the synergistic effect of soy and exercise shown in our study might be due to increased BDNF levels that promote several aspects of brain function.…”
Section: Discussionsupporting
confidence: 57%
“…It has been demonstrated that physical exercise increases BDNF levels 45. Thus, the synergistic effect of soy and exercise shown in our study might be due to increased BDNF levels that promote several aspects of brain function.…”
Section: Discussionsupporting
confidence: 57%
“…We observed that the peripheral administration of L-lactate did not lead to changes in either synaptogenesis, as defined as changes in PSD-95 or synaptophysin, within the STR, nor improve motor behavior. This in contrast to reports demonstrating that the administration of L-lactate to the hippocampus promotes both neurogenesis and improved cognitive behavior (Lev-Vachnish et al, 2019;Rice et al, 2002).…”
Section: Discussioncontrasting
confidence: 90%
“…The data shown in this study further support that microenvironmental changes in lactate can have a direct effect on NSC proliferation. Another recent publication observed increased numbers of newborn neurons with lactate injections, without effects on proliferation or early differentiation and without alteration in cognition (Lev-Vachnish et al, 2019). The dosing and exposure to lactate were different in these two studies.…”
mentioning
confidence: 87%